Takotsubo as Initial Manifestation of Non-Myopathic Cardiomyopathy Due to the Titin Variant c.1489G > T - Keller, Hans (Medicines (Basel), 2018)
Background: Whether patients with subclinical cardiomyopathy (CMP) are more prone to experience Takotsubo syndrome (TTS) than patients without CMP, is unknown. We present a patient with TTS as the initial manifestation of a hitherto unrecognized genetic CMP. Method: case report. Results: At age 55 after the unexpected death of her father, a now 61-year-old female had developed precordial pressure. Work-up revealed moderately reduced systolic function, dyskinesia of the interventricular septum, and indications for a TTS. Coronary angiography was normal but ventriculography showed TTS. Cardiac MRI confirmed reduced systolic function and TTS. TTS resolved without treatment and sequelae. At age 57 atrial fibrillation was recorded. After deterioration of systolic function at age 59 dilated CMP was diagnosed. Despite application of levosimendan, sacubitril, valsartan, and ivabradine, complete remission could not be achieved. Upon genetic work-up by means of a gene panel, the heterozygous mutation c.1489G > T (p. E497X) in exon 9 of the titin gene was detected and made responsible for the phenotype. Neurological work-up precluded involvement of the skeletal muscles. The further course was complicated by ventricular arrhythmias, requiring implantation of an implantable cardioverter defibrillator (ICD). Conclusions: previously subclinical CMP may initially manifest as TTS. Since patients with titin CMP are at risk of developing ventricular arrhythmias and thus to experience sudden cardiac death, appropriate anti-arrhythmic therapy needs to be established.